Extraction of archaeological information from metallic artefacts—A neutron diffraction study on Viking swords. (April 2017) - Fedrigo, Anna; Grazzi, Francesco; Williams, Alan R.; Panzner, Tobias; Lefmann, Kim; Lindelof, Poul Erik; Jørgensen, Lars; Pentz, Peter; Scherillo, Antonella; Porcher, Florence; Strobl, Markus
Abstract: Vikings (800–1050 CE) are famous for being fearsome seafarers and their weapons represented an indispensable tool in their plundering raids. Sword from the Viking age often showed pattern-welding, made by welding together thin strips of iron and steel that were twisted and forged in various ways, producing a decorative pattern on the surface. In this work we present a neutron diffraction study of three swords from the Viking age belonging to the National Museum of Denmark. This non-invasive approach was used to allow us to characterise the blades in terms of composition and manufacturing processes involved. The study shows how the effects of past conservation treatments can either help or obstruct the extraction of archaeological information. Highlights: Characterisation of metallurgical information of composite swords from the Viking Age from the National Museum of Denmark Non-destructive analysis by means of neutron diffraction based methods Shed light on past conservation treatments not recorded in the Museum inventory